The Labor Supply Response to (Mismeasured but) Predictable Wage Changes - French, Eric (The Review of Economics and Statistics, 2004)
Most panel data studies of intertemporal labor supply assume classical measurement error. Recent validation studies refute this assumption. In this study I address nonclassical measurement error explicitly. I use data on males from the Panel Study of Income Dynamics Validation Study to purge measurement error from the Panel Study of Income Dynamics. I find a large amount of predictable wage variation in the data, even after allowing for measurement error. However, there is almost no labor supply response to these predictable wage changes. Therefore, failure to control for nonclassical measurement error cannot explain the low estimated labor supply elasticities in other papers.